Part one;
when you say x-intercept , it means y must be 0 ; y = 0
if y = 0
3y=6x-9;
3*0 = 6x -9;
0 = 6x - 9;
6x = 9;
x = 9/6 ; x = 3/2
( 3/2 , 0 )
Part Two;
when you say y-intercept , it means x must be 0 ; x = 0
3y=6x-9
3y=(6*0)-9
3y = -9 ;
y = -9/3; y = -3
( 0 , -3)
Good Luck.
2006-09-10 10:40:05
·
answer #1
·
answered by sweetie 5
·
0⤊
1⤋
well let's see...
the y-intercept is when the line crosses the y-axis. The x value must be zero when the line crosses the y-axis, right? So... you just plug in a zero for x in your equation and work the algebra until you can isolate y on one side...
so, you say 3y=6x-9... so if x was zero, what would y be?
3y = 6(0)-9 (substitute zero for x)
3y = 0-9
3y = -9
y = -3 (divide everything by three)
OH! there you go... that's the y-intercept.
To get the x-intercept, you just do the same thing the other way around... plug in a zero for y instead... and then isolate x.
2006-09-10 17:30:23
·
answer #2
·
answered by boober 1
·
1⤊
0⤋
remove a factor of 3 to simplify the problem
y=2x-3. by inspection the y intercept is -3 and the x intercept is given by y=0 so
0=2x-3 giving that 2x=3 so x=1.5
2006-09-10 17:24:02
·
answer #3
·
answered by firstlennsman 1
·
1⤊
0⤋
3y=6x-9
y=2x-3
x-intercept: (3/2, 0)
y-intercept: (0, -3)
2006-09-10 17:16:24
·
answer #4
·
answered by spoof ♫♪ 7
·
1⤊
0⤋
x-intercept is when y = 0
0 = 6x-9
x = 3/2
y-intercept is when x = 0
3y = -9
y = -3
2006-09-10 17:17:47
·
answer #5
·
answered by Andy S 6
·
1⤊
0⤋
for y intercept put x=o
so y intercept=-3
for x intercept put y=0
x intercept=3/2
2006-09-10 17:17:54
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋
y intercept is -3
xintercept is 3/2
it think this is right
2006-09-10 17:19:39
·
answer #7
·
answered by apache1717 1
·
1⤊
0⤋
first you solve for y
-> y=2x-3
to find the x-int, set y=0
to find the y-int, set x=0
2006-09-10 17:19:28
·
answer #8
·
answered by KN 1
·
1⤊
0⤋